(untitled) (diségno, 2025)
The UID Symposium on Internationalisation and Research Innovation in Ferrara on 26th March is part of the 7th edition of the Days of Restoration and Cultural Heritage 2025. It aims to promote the internationalisation of research and its continuous innovation. [read more]